The struggle for the nation in Peru - Humala Tasso, Ulises (2008)
The advent of the republic did not bring any real improvement for the great ethnic groups. It was based on liberal principles and apparently had arguments against the servitude of the indigenous, but in practice it weakened the indigenous by attacking their community. The Peruvian population is mostly mestizo and Amerindian. In practice, the more intense and noticeable the indigenous traits of an individual, the greater the discrimination he suffers. A re-founding of the Republic is needed to definitively eliminate this discrimination.